Persepsi Guru Matematika terhadap Literasi Numerasi dan Pengaruhnya pada Pembelajaran di SMA - Rahmad Sugianto; Niswatun Hasanah; Mohammad Syaifuddin (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2023)
This study aims to determine the mathematics teacher's perception and its effect on literacy numeracy in high school. This research is descriptive qualitative. The population in this study were high school mathematics teachers. The sampling technique used is total sampling. A total of 30 teachers were sample correspondents spread across several high schools in Malang City. The data collection technique used was a questionnaire consisting of multiple choice, complex multiple-choice, and questions with yes or no answers, which aim to determine the mathematics teachers’ perception of literacy numeracy and its effect on learning in high school. Techniques for presenting data in descriptive statistics include tables and percentage calculations. The study’s results on the perception of mathematics teachers on literacy numeracy in high school showed an average of 67.58% with a positive interpretation level. Also, the effect of mathematics teachers' perceptions of literacy numeracy on learning in high school shows an overall average of 75.6% with a positive interpretation level.